Recommendations for Epstein-Barr virus–based screening for nasopharyngeal cancer in high- and intermediate-risk regions. (1st February 2023) - Lam, W K Jacky; King, Ann D; Miller, Jacob A; Liu, Zhiwei; Yu, Kelly J; Chua, Melvin L K; Ma, Brigette B Y; Chen, Ming Yuan; Pinsky, Benjamin A; Lou, Pei-Jen; Woo, John K S; Hsu, Wan-Lun; et al.
Abstract: A meeting of experts was held in November 2021 to review and discuss available data on performance of Epstein-Barr virus (EBV)–based approaches to screen for early stage nasopharyngeal carcinoma (NPC) and methods for the investigation and management of screen-positive individuals. Serum EBV antibody and plasma EBV DNA testing methods were considered. Both approaches were found to have favorable performance characteristics and to be cost-effective in high-risk populations. In addition to endoscopy, use of magnetic resonance imaging (MRI) to investigate screen-positive individuals was found to increase the sensitivity of NPC detection with minimal impact on cost-effectiveness of the screening program.